Imaging and photometric observations of proton aurora dynamics at Syowa Station,Antarctica - Takahashi, Yukihiro; Okano, Shoichi; Ono, Takayuki; Fukunishi, Hiroshi (National Institute of Polar Research, 1995)
P(論文) Using aurora data obtained with a multicolor all-sky imaging system (MAIS) and a tilting-filter photometer at Syowa Station (invariant magnetic lat., -66.1°), Antarctica, we have investigated the dynamics of proton auroras (Hβ emissions) and its relation to electron aurora dynamics. An all-sky SIT camera was also operated to monitor electron auroras. We obtained 4300 proton aurora images with MAIS on 29 nights in the period from May 1992 to September 1992. These data cover the magnetic local time sector from 14h to 4h and include various types of proton auroras in different substorm phases. It is found that when bright N-S auroras are seen in the bulge formed in an auroral breakup event, the region of proton aurora contracts poleward as the electron aurora in the bulge fades out, while when there are no N-S auroras in the bulge, the proton aurora remains equatorward. departmental bulletin paper